P-472 Extended oocyte cryostorage period is not associated with decreased post-warm survival rate: a retrospective study of 5208 vitrified/warmed oocytes at a single centre. (30th June 2022) - Craze, H; Odia, R; Cawood, S; Gaunt, M; Seshadri, S; Marvelos, D; Saab, W; Ozturk, O; Serhal, P
Abstract: Study question: Is extended oocyte cryostorage period associated with decreased post-warm survival rate? Summary answer: There is a weak inverse correlation between oocyte cryostorage duration and post-warm survival (r = 0.09, p = 0.01). This equates clinically to a reduction of 0.0003% survival/day. What is known already: It is widely reported that extended embryo storage is not associated with reduced post-warm survival rates, however there are no such studies in the literature relating to the effect of extended cryostorage duration on oocytes. Successful outcomes from oocyte vitrification are related to reduced patient age however UK government regulations only permit those with a medical indication to store and use their gametes over 10 years. With the intended extension of this 10-year limit, it is therefore fair for clinics to expect an increasing population of younger patients choosing to store their oocytes for longer periods. Study design, size, duration: A retrospective audit of all vitrified/warmed oocyte cycles at a single centre from 2014-2021. A total of 5208 oocytes were included in the study, from 602 treatment cycles. Participants/materials, setting, methods: Patients of all ages were included in the study. Data was obtained retrospectively from IDEAS V6.0 at CRGH, UK. All oocytes were vitrified/warmed according to the Irvine Scientific/Kitazato media protocols, with all other protocols excluded. Data was analysed using IBM® SPSS® Statistics V24. Kendall's tau-b and Spearman's Rho correlation coefficients measured the strength and direction of association between variables. A linear regression model was used to establish the effect of duration on survival per day. Main results and the role of chance: The median age at oocyte vitrification was 31 years (range 18-45 years, LQR=25 years, UQR=37 years). There was a median of 8 oocytes thawed per case (LQR=6, UQR 11 oocytes) with a median of 6 oocytes surviving (LQR=3, UQR=9 oocytes). The median survival rate across all ages was 81% (LQR=58%, UQR=100%). There was no significant difference in oocyte survival rate between age categories (<35 years vs > 35 years; p = 0.137, n = 414 & 188 respectively). Increasing age was however, significantly correlated with fewer oocytes vitrified (r = 0.283, p = 0.001). There is a weak inverse correlation between oocyte cryostorage duration and post-warm survival (r = 0.09). This correlation reaches statistical significance (p = 0.01), however this equates clinically to a reduction of 0.0003% survival rate per day. No significant difference was observed in post-warm oocyte survival rate across duration of vitrification categories (≤3 years vs 4-5 years vs > 5 years; p = 0.154, n = 416, 141 & 45 cases respectively). The median duration for which oocytes remained in cryostorage was 565 days (1.6 years) (LQR & UQR=233 days (0.64 years) and 1390 days (3.8 years) respectively). Limitations, reasons for caution: Although retrospective, the study benefits from many cycles, all of which were carried out at the same unit, using the same vitrification/warming media protocol. Limitations of this study include a relatively short median cryostorage duration time which could be masking the true effect of duration on post-warm oocyte survival. Wider implications of the findings: Following a public consultation in 2020 regarding the 10-year storage limit for gametes and embryos, the UK Government proposed changes the current legislation which will allow patients to extend cryostorage beyond 10 years without a medical indication. To our knowledge, this is the first study to lend support this movement. Trial registration number: IRB-001C03-01-22